Neurotransmitter-gated ion channels at fast chemical synapses: from structure to pathology - Bouzat, Cecilia (2005)
Ligand binding and channel gating are dynamic processes that require precise and coordinated movements of the protein, which have recently begun to be unraveled. Desensitization still remains a complex and mysterious process. If the goal of designing new ligands targeted to specific LGICs subtypes or to mutated receptors at the origin of the disease states is to be fulfilled, we require an intimate knowledge of the structure-function relationship of them. There is hope that the new understanding of the molecular pharmacology of Cys-loop receptors will led to a new generation of more selective drugs with improved safety profiles.